2021
DOI: 10.1111/jan.14869
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of smoking cessation interventions for smokers with chronic diseases: A systematic review

Abstract: Aims To systematically summarize seminal studies on the design and effectiveness of smoking cessation interventions targeted at patients with chronic diseases through a critical appraisal of the literature. Design A systematic review. Data Sources This review included literature identified through a search of six databases up to June 2020. Review Methods This review was conducted according to the Cochrane Handbook for Systematic Reviews of Interventions. The literature search was limited to English‐language ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(220 reference statements)
0
10
0
Order By: Relevance
“…Most importantly, instant messaging through applications is more flexible, efficient and time-saving than face-to-face meetings, particularly during pandemic, where the delivery of face-to-face health care interventions may not be feasible. Direct comparison with other previous trials may not be applicable owing to differences in types of mobile health intervention used, characteristics of target population and theoretical frameworks for study design ( 35 ). Nonetheless, the results of this study showed a higher odds of biochemically validated smoking abstinence at 6-month follow-up than that in a Cochrane meta-analysis of 12 trials on mobile health intervention for smoking cessation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, instant messaging through applications is more flexible, efficient and time-saving than face-to-face meetings, particularly during pandemic, where the delivery of face-to-face health care interventions may not be feasible. Direct comparison with other previous trials may not be applicable owing to differences in types of mobile health intervention used, characteristics of target population and theoretical frameworks for study design ( 35 ). Nonetheless, the results of this study showed a higher odds of biochemically validated smoking abstinence at 6-month follow-up than that in a Cochrane meta-analysis of 12 trials on mobile health intervention for smoking cessation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Continuation of smoking among patients with chronic diseases may also detrimentally affect health and treatment outcomes, increasing the risk of disease progression or recurrence and thus elevating the risk of mortality and reducing the efficacy of treatment [ 7 9 ]. The prevalence of smoking ranged from 15% to 26% among patients with chronic disease [ 10 ]. According to the World Health Organization [ 11 ], 14% of all deaths from chronic diseases were attributable to smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that the majority of Hong Kong Chinese with chronic diseases who smoke were in the precontemplation stage (i.e., no intention to quit) [ 19 ]; of these, 68% had cardiovascular disease [ 14 ], 70% had diabetes mellitus [ 16 ], and 73% had cancer [ 15 ]. A recent systematic review involving 10 interventional trials targeting adult smokers with chronic diseases found that the participant selection criteria in most studies excluded unmotivated smokers, indicating that most existing interventions and studies do not include the majority of smokers with chronic diseases [ 10 ]. This finding underscores the critical need for developing and evaluating appropriate smoking cessation interventions to promote smoking cessation targeting this population.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are associated with heavy smoking patterns characterized by an average of 19–24 cigarettes per day (Gilbody et al, 2019; Schnoll et al, 2004) and severe ND, especially in people with psychiatric disorders (Paik et al, 2019; Wang et al, 2021). These populations also struggle with withdrawal symptoms and exhibit lower cessation rates than the general population, even when evidence-based therapies are delivered (Ho et al, 2021; Secades-Villa et al, 2017). Consequently, it is particularly important to develop effective smoking cessation treatments specifically tailored to these populations (Ho et al, 2021; Prochaska & Benowitz, 2019).…”
mentioning
confidence: 99%
“…These populations also struggle with withdrawal symptoms and exhibit lower cessation rates than the general population, even when evidence-based therapies are delivered (Ho et al, 2021; Secades-Villa et al, 2017). Consequently, it is particularly important to develop effective smoking cessation treatments specifically tailored to these populations (Ho et al, 2021; Prochaska & Benowitz, 2019).…”
mentioning
confidence: 99%